L’eredità di Pareto ai tempi del populismo - Bianco, Adele (SocietàMutamentoPolitica, 2021)
Starting from the Transformation of Democracy (1921; engl. 1984), one of the last works by Pareto, this paper aims to highlight firstly the key aspects of the Pareto’s idea of politics and democracy, particularly concerning their functioning mechanism. Secondly, it helps to analyse the crisis of democracy and the populism wave experienced today by the advanced countries as well as the political situation in Italy. The paper is structured as follows. The first section is devoted to a Pareto’s profile as sociologist, trying to understand his historical, social and cultural framework. The second section is focused on his theoretical sociological activity and particularly on the distinction between logical and non-logical action. In the third section we are going to scrutinize the topic of the Transformation of Democracy. According to Pareto, the crisis of the sovereignty is due to the weakening of the State. It’s caused by the access to the power by those not qualified to be member of the ruling class. Consequently, the practice of democracy turns into spurious majorities, called by Pareto “demagogic plutocracy”. This kind of majorities manage power for their own benefit and not in favour of the whole community.